A twin of Polydora hoplura (Annelida: Spionidae) from the Arabian (Persian) Gulf, with review of primers used for barcoding of Spionidae - Radashevsky, Vasily I.; Al-Kandari, Manal; Malyar, Vasily V.; Pankova, Victoria V. (Zootaxa, 2024)
The spionid polychaete Polydora hoplura Claparède, 1868 has been widely recorded boring in shells of abalone, oysters, clams, barnacle tests and sponges in temperate and subtropical waters. Molecular studies have suggested conspecificity of individuals collected worldwide but showed high genetic variability of the species with the highest diversity of haplotypes in the South African population. We have compared the morphology and genetic data of shell-boring worms from Kuwait, which were previously assigned to P. hoplura, with American, Asian and European individuals, including those from the type locality in Italy. The Kuwaiti individuals share key diagnostic morphological characters with P. hoplura but differ in ochre pigment on the anterior chaetigers in life, pattern of pigmentation after fixation in formalin, and pattern of methyl green staining of fixed specimens. They also differ in the dimensions of mature spermatozoa. The analysis of sequence data of five gene fragments (total 3483 bp) showed that the intraspecific diversity of P. hoplura and the variability of Polydora individuals from Kuwait are less than the divergences in all studied genes, except for 28S rDNA, between these two groups. These data, as well as the absence of common cytochrome c oxidase subunit I (COI) and 16S haplotypes, and morphological differences between individuals from Kuwait and P. hoplura, allowed us to conclude that the Kuwaiti population is not conspecific with P. hoplura. This conclusion was confirmed by the results of the species delimitation analysis. In the Bayesian inference analysis of the sequence data individuals from Kuwait formed a well-supported clade sister to P. hoplura. These individuals are described and illustrated here as a new species, Polydora mohammadi sp. nov. Primers used for successful amplification of the mitochondrial COI gene in various species of Spionidae are reviewed and we suggest future studies on Polydora use a combination of two primer pairs (2F–spionid–LCO/1R–spionid–HCO and Dorid_COI.3F/Dorid_COI.1R) to target sequences that include the barcode fragments covered with “Folmer” and “Dorid” primers.